Reactivación del carbón activado del tipo calgon americano 6x12 utilizado en la Sociedad Minera Promine para el proceso de adsorción de metales preciosos - Lapo Alverca, Junior A. (2014)
This research is based on the chemistry of the activated carbon reactivation American calgon 6 x 12 type used in the mining company PROMINE for the adsorption of precious metals. For the development of this work was implemented a preliminary stage , which consisted of the preparation of the various reagents used in the various tests of chemical recovery.